2015
DOI: 10.1103/physrevd.92.094022
|View full text |Cite
|
Sign up to set email alerts
|

Interacting ensemble of the instanton-dyons and the deconfinement phase transition in the SU(2) gauge theory

Abstract: Instanton-dyons, also known as instanton-monopoles or instanton-quarks, are topological constituents of the instantons at nonzero temperature and holonomy. We perform numerical simulations of the ensemble of interacting dyons for the SU(2) pure gauge theory, using standard Metropolis Monte Carlo and integration over parameter methods. We calculate the free energy as a function of the holonomy (logarithm of the Polyakov line) , the dyon densities, and the Debye mass, and find its minima as a function of those p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 30 publications
3
59
0
Order By: Relevance
“…These results inspired various lattice studies, which exhibit remarkable matching to the theoretical predictions [127][128][129][130]. The semi-classically calculable realization of center-symmetry also inspired related works in the strong coupling regime, see [122,124,125], and lattice simulations [126].…”
Section: Calculability and The Deconfinement Phase Transitionmentioning
confidence: 92%
“…These results inspired various lattice studies, which exhibit remarkable matching to the theoretical predictions [127][128][129][130]. The semi-classically calculable realization of center-symmetry also inspired related works in the strong coupling regime, see [122,124,125], and lattice simulations [126].…”
Section: Calculability and The Deconfinement Phase Transitionmentioning
confidence: 92%
“…Their mechanism has been discussed extensively since the 1970's: We will mention some historical highlights below. Our previous papers, to be referred to as I [1] and II [2] below, addressed those phenomena in a model based on a certain gauge topology model.…”
Section: Introductionmentioning
confidence: 99%
“…This observation lead to the proposal [12] of confinement being driven by this effect, and in a very specialized setting it has been shown to induce confinement [25,26], even for exponentially small dyon density. Recent works using mean field methods [27,28] and our own two papers [1,2] had shown that sufficiently dense ensemble of the dyons does generate both confinement and chiral symmetry breaking, with close transition temperatures (too close to separate inside the errors).…”
Section: Introductionmentioning
confidence: 99%
“…The case of no fermions [1] is strongly affected by the breaking of center symmetry. In terms of dyons, breaking of center symmetry is observed as the density of M and L type dyons becoming different.…”
Section: Flavorsmentioning
confidence: 99%